China its environment and history - Marks, Robert, 1949- (World social change., 2012)
This book provides a comprehensive and comprehensible history of China from prehistory to the present. Focusing on the interaction of humans and their environment, the author traces changes in the physical and cultural world that is home to a quarter of humankind. Through both word and image, this work illuminates the chaos and paradox inherent in China's environmental narrative, demonstrating how historically sustainable practices can, in fact, be profoundly ecologically unsound. The author also reevaluates China's traditional "heroic" storyline, highlighting the marginalization of nature that followed the spread of Chinese civilization while examining the development of a distinctly Chinese way of relating to and altering the environment. And also, he makes the compelling argument that all of humanity has a stake in China's environmental future.